Analisa Proses Drawing Pada Pembentukan Asbak Dengan Kuping Berbentuk Alur - Idiar Idiar; Sugianto Sugianto (Manutech : Jurnal Teknologi Manufaktur, 2017)
The design of the press tool is one of the practice courses that teach the skill in designing tool forming and cutting the product from the plate. The quality of the design is determined by the ability to apply the design procedure. Competence is widely applied in the design of drawing prints with a certain level of product complexity. Practice activity of designing drawing drawing of students of Engineering Design Program of Mechanical Polytechnic of State of Bangka Belitung done conventionally, where only using drawing table or computerized depiction software then printed on drawing paper. This results in frequent errors in student design drawings. To overcome these problems required drawing prints that can form a specific product such as ashtrays, with the aim of producing a construction drawing print that can be applied and utilized in the teaching of press tool design. The method of making this tool consists of data collection, concept making, tool design, machining & testing. Based on the results of trials that have been done, carried out on 10 blank by using a lubricant in the form of vegetable oil. Of the 10 experiments the formation showed that the central pool of ashtrays can be perfectly formed, while 4 pieces of the grooves on the ear of the ashtray have not been formed well where there are still folds or curves that are not regular.